Evaluation of processes driving iodine monoxide and ozone variability over the Western Pacific warm pool - Takashi Sekiya; Hisashiro Takashima; Yugo Kanaya; Fumikazu Taketani; Kengo Sudo; Martina M. Friedrich; Michel Van Roozendael (Progress in Earth and Planetary Science, 2025)
Abstract Iodine chemistry exerts a nonnegligible influence on tropospheric ozone depletion over oceanic regions. The impact of iodine has been extensively studied using three-dimensional chemical transport models (CTMs). However, the factors governing the variability of iodine monoxide (IO) and ozone in the marine boundary layer (MBL) remain uncertain. This study examines the impact of fine-scale meteorological variability and ozone-independent iodine sources on the MBL IO and ozone concentrations over the Western Pacific Warm Pool (WPWP) through ship-borne observations and high-resolution CTMs during November–December 2014. The high (0.56 $$^°$$ ∘ )-resolution model demonstrates a negative correlation between IO and ozone at the observation locations ( $$r = -$$ r = - 0.45), which is more closely aligned with that derived from the ship-borne observation data ( $$r = -$$ r = - 0.70) than the coarse (2.8 $$^°$$ ∘ )-resolution model ( $$r =$$ r = 0.08). Sensitivity analysis indicates that a contrast in the correlation between the 0.56 $$^°$$ ∘ and 2.8 $$^°$$ ∘ resolutions emerges from the interplay of fine-scale atmospheric transport and chemistry processes, rather than from fine-scale atmospheric transport solely or ozone-dependent oceanic iodine release. This interplay leads to a greater ozone loss mediated by the iodine cycle at 0.56 $$^°$$ ∘ resolution (by 0.56 ppbv day $$^{-1}$$ - 1 ) compared to that at 2.8 $$^°$$ ∘ resolution (by 0.20 ppbv day $$^{-1}$$ - 1 ), due to the reduced mixing with air outside the MBL over the WPWP at finer resolution. Furthermore, incorporating ozone-independent iodine sources such as photolysis of $${\text{CH}_{2}\text{I}_{2}}$$ CH 2 I 2 , $${\text{CH}_{2}\text{IBr}}$$ CH 2 IBr , and $${\text{CH}_{2}\text{ICl}}$$ CH 2 ICl enhances the IO-ozone anti-correlation coefficient (−0.50). These findings highlight the critical roles of interplay of the fine-scale atmospheric transport and chemistry processes and oceanic ozone-independent iodine sources in the co-variability of IO and ozone over the WPWP.